2020
DOI: 10.3390/molecules25081937
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic-Hydroxy and Carboxy Functionalization of Alkyl Moieties in Drug Molecules: Prediction of Structure Influence and Pharmacologic Activity

Abstract: Alkyl moieties—open chain or cyclic, linear, or branched—are common in drug molecules. The hydrophobicity of alkyl moieties in drug molecules is modified by metabolic hydroxy functionalization via free-radical intermediates to give primary, secondary, or tertiary alcohols depending on the class of the substrate carbon. The hydroxymethyl groups resulting from the functionalization of methyl groups are mostly oxidized further to carboxyl groups to give carboxy metabolites. As observed from the surveyed cases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…The precursor ion identified as [M-H] − at m / z 485.33 ( M3 ) has a Mw 30 Da more than BA, corresponding to the addition of 2 O atoms while eliminating 2 H atoms. This second step of the oxidation reaction most likely altered the already available hydroxymethyl substituent; the end result of this two-step oxidation is the conversion of the methyl substituent to carboxyl, generating an inactive metabolite, as previously reported [ 23 , 32 ]. Furthermore, the MS screening spectrum indicated also the formation of the precursor ion at m / z 487.34 ( M4 ), which has a Mw 32 Da more than BA, corresponding to the addition of two O atoms as a result of a two-site hydroxylation metabolic reaction, most likely converting two methyl substituents to hydroxymethyl ones.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…The precursor ion identified as [M-H] − at m / z 485.33 ( M3 ) has a Mw 30 Da more than BA, corresponding to the addition of 2 O atoms while eliminating 2 H atoms. This second step of the oxidation reaction most likely altered the already available hydroxymethyl substituent; the end result of this two-step oxidation is the conversion of the methyl substituent to carboxyl, generating an inactive metabolite, as previously reported [ 23 , 32 ]. Furthermore, the MS screening spectrum indicated also the formation of the precursor ion at m / z 487.34 ( M4 ), which has a Mw 32 Da more than BA, corresponding to the addition of two O atoms as a result of a two-site hydroxylation metabolic reaction, most likely converting two methyl substituents to hydroxymethyl ones.…”
Section: Resultsmentioning
confidence: 57%
“…The screening of plasma samples revealed the presence of the [M-H] − ion at m / z 457.37 ( M1 ), which has a molecular weight (Mw) 2 Da more than BA, corresponding to the addition of 2 H atoms and was assigned according to the mass calculations to the product of a hydrogenation reaction by double bond reduction occurring at the isopropenyl group (C 20 -C 29 ) of ring E. Hydrogenation is a common metabolic reaction reported both for human steroid metabolism and for the metabolism of phytochemicals that bear double bonds in their structure, such as flavonoids [ 29 ], terpenes [ 30 ] or phenylpropanoid glycosides [ 31 ]. Next, the precursor ion identified as [M-H] − at m / z 471.35 ( M2 ) has a Mw 16 Da more than BA, corresponding to the addition of an O atom as a result of a metabolic reaction that modified most likely one of the methyl substituents to hydroxymethyl, as reported both for medicinal drugs [ 32 ] and phytocompounds [ 23 ]. Hence, m / z 471.35 was assigned as the monohydroxylated metabolite of BA.…”
Section: Resultsmentioning
confidence: 99%
“…S2), these metabolites were formed by P450s in a regio-or stereospecific manner. Some drugs such as glipizide and glibenclamide also possess a cyclohexane ring and the formation of their isomerized hydroxylated P450 metabolites was reported (Rupp et al, 1969;Sugihara et al, 1975;Zharikova et al, 2007 andEl-Haj et al, 2020). Incubation of DS-1971a with liver microsomes from various species suggested that HLM showed the highest metabolic activity to form M1 and the dominant metabolite in mouse, rat, monkey and dog liver microsome included metabolites other than M1 (i.e., M2, M1/M5, M2, and M2, respectively) (Fig.…”
Section: Inhibitory Potential Of Ds-1971a and M1 On Cyp2c8 Activity In Hlmmentioning
confidence: 99%
“…Considering this effect, Δ9-tetrahydrocannabinol ( 68 ) is a psychoactive constituent from Cannabis sativa L. THC has a great homeostatic influence on the central nervous system (CNS). The carbon C11 is oxidized to a hydroxymethyl metabolite, 11-hydroxy-Δ-9-tetrahydrocannabinol ( 69 ), responsible for the most pharmacological effects ( Supplementary Schemes 6S, 9S ) ( Sharma et al, 2012 ; Mechoulam et al, 2014 ; El-Haj and Ahmed, 2020 ).…”
Section: Analog Design Effects Of Hydroxymethylation On Drug/bioactiv...mentioning
confidence: 99%